Aerosolized Insecticide Spray Distributions and Relationships to Efficacy against Stored Product Pests - Daniel Brabec; Srinivas Lanka; James F. Campbell; Frank H. Arthur; Deanna S. Scheff; Kun Yan-Zhu (Insects, 2023)
Aerosol insecticides are widely used in stored product insect management programs in food facilities. Previous research has shown spatial variation in aerosol efficacy within facilities, but information on how spatial patterns of aerosol droplet concentration, size distribution, dispersal, and deposition contribute to this variation in efficacy is limited. This study involved two aerosol application systems: a high-pressure cylinder containing TurboCide Py-75® with pyriproxyfen IGR (ChemTech Ltd., Des Moines, IA, USA) and a hand-held fogger containing Pyrocide 100® (MGK, Minneapolis, MN, USA) with Diacon II which contains methoprene IGR (Wellmark, Schaumburg, IL, USA). These systems were used at single or multiple application locations. The spray trials were conducted in a small-scale flour mill, Hall Ross Flour Mill (Kansas State University, Manhattan, KS, USA). The droplet size distributions were monitored at multiple positions within the room using nine aerodynamic particle sizing (APS, TSI Incorp, Shoreview, MN, USA) instruments. The APS data collected over the treatment period were summarized into a mass concentration index (MCI), which ranged from 155 to 2549 mg/m3 for Turbocide and 235–5658 mg/m3 for Pyrocide. A second parameter called the Deposition Index (Dep.Idx) was derived to estimate potential insecticide depositions on the floor and has units of g/m2. The Dep.Idx was below 5.3 g/m2 for most Turbocide applications, while the Dep.Idx was below 8.4 g/m2 for most Pyrocide applications. The MCI and Dep.Idx values varied with APS position and spray application location, with proximity to the aerosol application location and degree of obstruction between the release point and APS position contributing to this variation. We assessed the relationship between aerosol droplet parameters and insect efficacy using Tribolium confusum Jacqueline DuVal, the confused flour beetle. The adults were treated directly, while the larvae were treated two weeks later during the residual test (previously published). For Turbocide, efficacy against adults increased with MCI and Dep.Idx values, but for residual efficacy of the IGR, efficacy was high at all aerosol droplet values, so no relationship was apparent. In contrast, the relationship between Pyrocide deposition and adult insect efficacy was highly variable. But with larval insect efficacy, residual larvae control was directly related to increases in Pyrocide MCI and Dep.Idx. Contour plots of Dep.Idx values were developed, which could be used to predict areas of the mill that are not receiving an adequate application rate, and this could be used to develop more effective application strategies for aerosol insecticides in food facilities.